Polyelectrolyte multilayered assemblies in biomedical technologies - Costa, Rui R. (2014)
Layer-by-layer (LbL) was first introduced as a surface modification technique based on the sequential spontaneous adsorption of at least two distinct materials onto planar substrates. In the last two decades, this technique has been expanded to the coating of more convoluted geometries with high levels of tailored functionalization or with structural purposes. In this review, the potential uses of LbL films in biomedical engineering based mainly on the assembly of polyelectrolytes are reviewed. Examples of recent developments are provided, from the modification of substrates to improve their biointegration or to add specialized properties, to the three-dimensional extrapolation of this technique to more complex structures for cell seeding, drug delivery devices, biosensors and customizable microreactors. Future strategies and opportunities are compared with current medical and laboratorial methodologies. Through them, it is expected that LbL will contribute greatly to the development of new functional devices with high perspectives of return for the administration of active agents, supports for cells in regenerative medicine and tissue engineering, biosensing and construction of microtissues and disease models in the laboratory.